Shape Memory Composites Based on a Thermoplastic Elastomer Polyethylene with Carbon Nanostructures Stimulated by Heat and Solar Radiation Having Piezoresistive Behavior - Zapata-Ramirez, P (John Wiley and Sons Ltd, 2018)
A thermoplastic elastomer polyethylene (TEPE) based on an ethylene/1-butene copolymer having shape memory effect (SME) without any chemical modification is presented and the effect of adding either carbon nanotubes or thermally reduced graphite oxide is analyzed. For electrical percolated samples, the development of a polymer sensor that changes its electrical conductivity under solar radiation triggered by SME is further presented. Our results showed that programmed samples recovered their permanent shape showing SME under a direct heating stimulus at 60 °C. The addition of carbon nanostructures increased the times needed to reach 100% recovery as compared with pure TEPE. Noteworthy, the SME was also stimulated remotely by solar radiation increasing the sample temperature. Composites presented a faster SME under this remote radiation process as compared with pure TEPE due to their higher radiation absorption. Percolated TEPE/carbon nanotube composites displayed further a decrease in the electrical resistivity during SME under this solar radiation. Finally, our results showed that the glass transition also triggered the SME in these samples allowing the development of triple shape memory polyethylenes without any chemical crosslinking process. Based on these findings, a simple route was developed to produce double, or even triple, shape memory piezoresistive polyethylenes that can be activated remotely by solar radiation. © 2018 Society of Chemical Industry. © 2018 Society of Chemical Industry
Keywords: polymer composites; nanocomposites; smart polymers